Consumer behavior - Schiffman, Leon G.; Kanuk, Leslie Lazar; Wisenblit, Joseph (Pearson Education, 2010)
Taking a market segmentation approach, this latest edition of a respected text carefully balances consumer behaviour concepts, research and applied marketing examples.